Transmuscular quadratus lumborum block for percutaneous nephrolithotomy: Study protocol for a dose‐finding trial. Issue 8 (30th April 2020) - Andersen, Christian H. S.; Laier, Gunnar H.; Nielsen, Martin V.; Dam, Mette; Hansen, Christian K.; Tanggaard, Katrine; Børglum, Jens
Abstract : Background: The objective of this trial is to optimize the transmuscular quadratus lumborum (TQL) block, by investigating the minimal effective volume (MEV90 ) of ropivacaine 0.75% for single‐shot TQL block in percutaneous nephrolithotomy (PNL) patients. Methods: This double‐blind, randomized and controlled dose‐finding trial is based on a biased coin up‐and‐down sequential design, where the volume of local anaesthetic administered to each patient depends on the response from the previous one. Investigating the TQL block, the first patient recruited receives 20 ml ropivacaine 0.75% preoperatively. In case of block failure, the next patient will receive the same volume with an increment of 2 ml. Given a successful block for the first patient, the next patient will be randomized to either a lower volume (previous volume with a reduction of 2 ml), or the same volume as the previous patient. The respective probabilities being b = 0.11 for a reduced volume and 1‐b = 0.89 for the same volume. Block success is defined as patient reported pain score numeric rated scale (NRS) ≤3 (0‐10/10) 30 minutes after arrival in the post anaesthesia care unit (PACU). The NRS pain score is our primary and only outcome for block success. A minimum of 25 eligible patients are needed to achieve precise estimation of MEV90 with narrow 95% confidence intervals derived by bootstrapping. Discussion: Recruiting will begin June 2020 and is expected to finish November 2020. Data analysis will be performed at interims during and after the study. Results will be published in an international peer‐reviewed medical journal.